Sea Level and Shallow Water Current Variability in Pagasa Island, Philippines - Villanoy, Cesar; Mancebo, Fay (Science Diliman: A Journal of Pure and Applied Sciences; Vol 10 No 2 (1998), 2007)
Significant wave height, sea level, and currents at 0, 2, 4, and 6m were measured using a doppler current meter deployed at the northern reef of Pagasa Island from 16 October 1997 to 3 March 1998. Tidal components of sea level and current data were extracted using harmonic analysis and subtracted from the original series to obtain residuals. These were then correlated with each other and with atmospheric variables (wind speed and atmospheric pressure). The tidal components accounted for about 98% of the variance in sea level but only 4-5% of the variance in the currents. Power spectral density correlations indicate that residual sea level variations may be due to set-up by wave action. Strong non-tidal residual components of the flow suggest conditions favorable for offshore transport which may promote long-distance dispersal of propagules.
Keywords: reef circulation, current and sea level variability, Pagasa Island, Kalayaan Island Group